Increasing use of artemisinin-based combination therapy for treatment of malaria infection in Nigerian hospitals - Igboeli NU; Ukwe CV; Ekwunife OI (Centro de Investigaciones y Publicaciones Farmaceuticas, 2010)
Objectives: This study aimed at describing the pattern of outpatient antimalarial drug prescribing in a secondary and a tertiary hospital, and to assess adherence to the National Antimalarial Treatment Guideline (ATG). Methods: An audit of antimalarial prescription files from the two health facilities for a period of six months in 2008 was conducted. Semi structured questionnaires were used to collect information from the doctors and pharmacists on their awareness and knowledge of the National Antimalarial Treatment Guideline. Results: Artemisinin-based combination therapies (ACTs) were the most prescribed antimalarials. Overall, 81.4% of the total prescriptions contained ACTs, out of which 56.8% were artemether-lumefantrine. However, adherence to the drugs indicated by national guideline within the DU90% was 38.5% for the tertiary and 66.7 % for the secondary hospital. The standard practice of prescribing with generic name was still not adhered to as evidenced in the understudied hospitals. The percentage of health care providers that were aware of the ATG was 88.2% for doctors and 85.1% for pharmacists. However, 13.3% and 52.2% of doctors and pharmacists respectively could not properly list the drugs specified in the guideline. Amodiaquine was the most commonly preferred option for managing children aged 0 - 3 months with malaria infection against the indicated oral quinine.Conclusion: This study showed an increased use of artemisinin-based combination therapy for the treatment of uncomplicated malaria compared previous reports in Nigeria. This study also highlights the need for periodic in-service quality assurance among health professionals with monitoring of adherence to and assessment of knowledge of clinical guidelines to ensure the practice of evidence based medicine.